2017
DOI: 10.1186/s12889-017-4242-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ebola outbreak on routine immunization in western area, Sierra Leone - a field survey from an Ebola epidemic area

Abstract: BackgroundSince March 2014, the Ebola Virus Disease (EVD) outbreak in West Africa disrupted health care systems - especially in Guinea, Liberia and Sierra Leone – with a consequential stress on the area’s routine immunization programs. To address perceived decreased vaccination coverage, Sierra Leone conducted a catch-up vaccination campaign during 24–27 April 2015. We conducted a vaccination coverage survey and report coverage estimates surrounding the time of the EVD outbreak and the catch-up campaign.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…The arrival of the new coronavirus drew attention away from the measles outbreaks and has the potential to compromise programs against other pre-existing diseases and epidemics, such as tuberculosis and malaria. The same happened during the Ebola epidemic 10 . The Strategic Advisory Group of Experts on Immunization (SAGE/WHO) advised that all mass vaccination campaigns in the world should be suspended during the pandemic.…”
Section: Introductionmentioning
confidence: 74%
“…The arrival of the new coronavirus drew attention away from the measles outbreaks and has the potential to compromise programs against other pre-existing diseases and epidemics, such as tuberculosis and malaria. The same happened during the Ebola epidemic 10 . The Strategic Advisory Group of Experts on Immunization (SAGE/WHO) advised that all mass vaccination campaigns in the world should be suspended during the pandemic.…”
Section: Introductionmentioning
confidence: 74%
“…For example, the Ebola virus outbreak severely affected the capacity to deliver early child intervention programs, including vaccinations. 18 The result was a wave of inadequately protected children. Similarly, transfer of personnel and resources from obstetric and neonatal services will increase perinatal complications.…”
Section: Methods For Consensus Statementsmentioning
confidence: 99%
“…Sun et al, conducted a study in West Africa post EBV outbreak and compared vaccination coverage of pentavalent and Measles pre outbreak, during the outbreak and post MCHW campaign found a decrease of 29.6% in Penta-3 and decrease of 25.9% in measles coverage during pandemic which rose post campaign but not to statistically significant level. 12 A massive decrease has been found in DPT 2nd booster coverage which is due at 5 years of age as per National immunization schedule, re-emphasizing the parents lack of concern for booster doses as against the fear of exposure to COVID infection. Similar findings were reported by Patel et al 8 Many studies have shown that VPD outbreaks especially measles epidemics often follow humanitarian crises.…”
Section: Discussionmentioning
confidence: 99%